STUDI TENTANG PENGELOLAAN PASAR TRADISIONAL PADA UNIT PASAR SURUH KABUPATEN SEMARANG - Nur Fitriyati; Muhammad Adnan; Teguh Yuwono (Journal of Politic and Government Studies, 2017)
The need for good traditional market management as well as the problems occurring in the management of traditional markets into the background of this research. Problems arise: How is the conflict of interest between the Regency Government and the Village Government in the management of Suruh Market Semarang regency? What are the social and economic impacts of conflict of interest between the Regency Government and the Village Government in the management of Suruh Market Semarang regency?The purpose of this study is to explain how the process of conflict of interest in the management of traditional markets is Suruh Market between the Regency Government and Village Government. In addition to describe and analyze the impacts resulting from the conflict of interest in the management of traditional markets, especially Suruh Market viewed from the social and economic aspects.This study uses a combined research method between qualitative and quantitative with a qualitative approach fixed as the main approach. Data obtained through interviews and questionnaires. The data obtained from the quantitative approach through the survey is used to reinforce the facts related to the theme and the formulation of related problems. In addition, using Triangulation data sources to compare the results of interviews with one another.The result of the research shows that conflict of interest occurs because of different interests between parties involved. Regency Government, Village Government and Traders have a mutually striving interest. Conflict of interest occurs when the Regency Government wants to take over and manage the Suruh Market completely but there is a rejection by the Village Government. The social impact that occurs is the decline in the number of traders and competition among traders is getting tougher. While the economic impact is a decline in the turnover of traders.Keywords: Management, Traditional Market, Interest